SOSIALISASI DIGITAL MARKETING UNTUK PENINGKATAN KINERJA PEMASARAN PRODUK BUMDESA SEHATI SERAMBUT DI KOTAWARINGIN TIMUR - Toepak, Erwin Prasetya; Kristinae, Vivy; Supriyono , Bambang; Sopather, Kembara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Serambut Village, Pulau Hanaut District, East Kotawaringin has local resource-based economic potential, one of which is the coconut oil business unit managed by BUMDesa Sehati Serambut. Although it has potential products, the marketing strategy implemented has not utilized digital channels optimally. The use of digital channels is very necessary to expand market reach and strengthen the competitiveness of BUMDesa products in the digital era. This community service activity was carried out as a response to these needs with the main objective of increasing the knowledge and basic skills of BUMDesa employees in utilizing social media and e-commerce platforms as marketing tools. This activity was carried out in the form of interactive socialization and open discussions that emphasized understanding the concept of digital marketing based on the 4P theory (Product, Price, Place, Promotion). The activity methodology involved delivering materials and participatory dialogue between speakers and participants. Initial results showed high enthusiasm from participants and increased awareness of the importance of digital transformation in marketing. This socialization is targeted to produce outputs in the form of increased digital marketing literacy among BUMDesa actors, as well as being a basis for further mentoring activities. By delivering the material appropriately and contextually, this activity is expected to have a long-term impact in increasing the institutional capacity of BUMDesa and the competitiveness of local digital-based products.